The Role of Browsing in The Relationship Between Online Reviews to Impulse Buying - Astuti, Rifelly Dewi; Nindyaswari, Sara Almira (ASEAN Marketing Journal, 2022)
Manuscript type: Research Research Aims: to analyse the impact of online reviews on Instagram on online impulse buying behaviour for the beauty product category, with the role of browsing as a mediator. Design/methodology/approach: A conclusive study with 441 respondents, analysed by SEM Research Findings: Browsing mediates the online review perceived value (both utilitarian and hedonic value) significantly toward the urge to buy impulsively, which will further enhance the impulse buying Theoretical Contribution/Originality: (1) this study enriches the relationship between online reviews and impulse buying, using browsing as the critical factor to link the relationship, and (2) consumers perceived both utilitarian and hedonic value in online reviews. Practitioner/Policy Implication: this study highlights the importance of online reviews in affecting the customer's online impulse buying behaviour, so brand marketers should monitor online product reviews, both positive and negative. Research limitation/Implications: First, this study only examined consumers' browsing and impulse buying behaviour toward online reviews on Instagram; thus, studies on social media platforms might have different results. Second, the antecedents of browsing are limited to the utilitarian and hedonic value of online review; other external variables could be further investigated to enrich our understanding. Lastly, this study is limited to the beauty product industry; another specific context might have a different result.